(untitled) - Feynman, Richard P. (Cambridge, 1987)
Developing a theory that seamlessly combines relativity and quantum mechanics, the most important conceptual breakthroughs in twentieth century physics, has proved to be a difficult and ongoing challenge. This book details how two distinguished physicists and Nobel laureates have explored this theme in two lectures given in Cambridge, England, in 1986 to commemorate the famous British physicist Paul Dirac. Given for nonspecialists and undergraduates, the talks transcribed in Elementary Particles and the Laws of Physics focus on the fundamental problems of physics and the present state of our knowledge. Professor Feynman examines the nature of antiparticles, and in particular the relationship between quantum spin and statistics. Professor Weinberg speculates on how Einstein's theory of gravitation might be reconciled with quantum theory in the final law of physics. Highly accessible, deeply thought provoking, this book will appeal to all those interested in the development of modern physics.
Keywords: Quantum theory,Lý thuyết lượng tử